Identifikasi Nilai Tambah Pelaku Rantai Pasok Komoditas Kentang di Kecamatan Pangalengan Kabupaten Bandung - Dandi Taryadi; Ade Yunita Mafruhat (UNISBA Press, 2023)
Abstract. Pangalengan sub-district is a production center for potato commodities in Bandung regency. The land is fertile and superior in the production of potato commodities as a superior commodity. One of the problems faced is the supply chain process which is too long which causes the selling price of potatoes to be low. The purpose of this study was to find out the parties involved in the potato commodity supply chain, and to find out the added value received by each chain actor for the potato commodity in Pangalengan District. The method used in this study is a qualitative method and the Hayami method to calculate added value, the data used is primary data. The results of the study show that the supply chain for potato commodities is relatively effective because all parties get added value. The suggestion of this research is the need to increase the role of institutions, government and cooperation between chain actors so that added value can be maximized. Keywords: Supply Chain, Value Added, Potato. Abstrak. Kecamatan Pangalengan adalah sentra produksi komoditas kentang di Kabupaten Bandung. Tanahnya yang subur dan unggul dalam produksi komoditas kentang sebagai komoditas unggulan, Salah satu masalah yang dihadapi yaitu proses rantai pasok yang terlalu panjang sehingga membuat harga jual kentang rendah. Tujuan penelitian ini adalah untuk mengetahui pihak yang terlibat dalam rantai pasok komoditas kentang, dan untuk mengetahui nilai tambah yang diterima masing-masing pelaku rantai pada komoditas kentang Kecamatan Pangalengan. Metode yang digunakan dalam penelitian ini adalah metode kualitatif dan metode Hayami untuk menghitung nilai tambah, data yang digunakan data primer. Dari hasil penelitian menunjukkan bahwa rantai pasok pada komoditas kentang relatif efektif karena semua pihak memperoleh nilai tambah. Saran penelitian ini adalah perlunya peningkatkan peran kelembagaan, pemerintah dan kerjasama antar pelaku rantai supaya nilai tambah dapat dimaksimalkan. .